2011
DOI: 10.1016/j.kjms.2011.06.012
|View full text |Cite
|
Sign up to set email alerts
|

The effects of labor on differential gene expression in parturient women, placentas, and fetuses at term pregnancy

Abstract: Labor and its associated pain are thought to have unique impacts on parturient women. The goal of this study was to investigate the effects of labor and associated pain on differential gene expression profiles in the maternal, fetal, and placental compartments. We used microarrays to analyze maternal blood (MB), fetal cord blood (CB), and placental tissue samples in pregnant women after term vaginal deliveries (laboring group) and in term pregnant women after scheduled Ceasarean sections (nonlaboring group). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
15
0
1
Order By: Relevance
“…Such observations can be explained by the T1 and T2 placentae being closer in gestational age than term placentae (Table 1) and, hence, more similar in developmental processes. Additionally, induction of parturition-responsive genes can alter placental gene expression as the organ reaches term (Peng et al, 2011). Hence, at earlier gestational ages (T1 and T2), fetal drug exposure to transporter substrates may be more similar than at term.…”
Section: Discussionmentioning
confidence: 99%
“…Such observations can be explained by the T1 and T2 placentae being closer in gestational age than term placentae (Table 1) and, hence, more similar in developmental processes. Additionally, induction of parturition-responsive genes can alter placental gene expression as the organ reaches term (Peng et al, 2011). Hence, at earlier gestational ages (T1 and T2), fetal drug exposure to transporter substrates may be more similar than at term.…”
Section: Discussionmentioning
confidence: 99%
“…All the pregnant women were free of hypertension, diabetes mellitus, preterm labor, and other medical diseases. All neonates were born at term and with normal body weight and healthy vital signs that were evaluated with Apgar scores at 1 min and 5 min after delivery, as used previously [42][44].…”
Section: Resultsmentioning
confidence: 99%
“…Eleven normal placental tissues were obtained from 9 healthy individuals who underwent cesarean section without labor pain [42]. This study was approved by the Institutional Review Board of Chang Gung Memorial Hospital (IRB#96-0630B).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, a number of studies have reported differences in gene expression between labouring and non-labouring placentas [26–29] , which may arise from a decrease in placental oxygen supply during contractions [10] and/or differences in exposure to hormones associated with labour [30] . PHLDA2 is known to be responsive to hypoxia [31–33] but it is not known whether placental expression of PHLDA2 , CDKN1C , PEG3 or PEG10 is altered in response to labour.…”
Section: Introductionmentioning
confidence: 99%